Somatic embryogenesis and transgenic development in black pepper for delayed infection and decreased spread of foot rot caused by Phytophthora capsici - Sinoj, J.; Sheeja, T.E.; Bhai, R.S.; Suraby, E.J.; Minoo, D.; Soji, J.; Jayakumar, V.N.; Anandaraj, M.; Bansal, K.C.; Babu, K. Nirmal (Journal of Plantation Crops, 2014)
Phytophthora capsici causing Phytophthora foot rot is the most important pathogen of black pepper (Piper nigrum L.). With a view to develop transgenic plants with resistance to this pathogen, Agrobacterium mediated genetic transformation using a PR 5 (pathogenesis related) gene ‘osmotin’ was attempted. Initially protocols for plant regeneration and somatic embryogenesis were optimised. Murashige and Skoog (MS) and woody plant media (WPM) supplemented with benzyl adenine (BA) (0.05-1 mg l-1) and thidiazuron (TDZ) (0.05-1 mg l-1) was found to be ideal. Plants could be successfully regenerated from tender leaf, shoot tip and hypocotyl explants of both mature and juvenile tissues. Somatic embryogenesis was also induced successfully from tender leaf explants of in vitro established mature tissues using the same medium. Successful transformation of leaf explants from these somatic embryo derived plants using Agrobacterium strain pGV 2260 carrying ‘osmotin’ under the control of CaMV 35S promoter was achieved. About 50 putative transgenic plants were obtained and planted in the green house. The gene transfer was confirmed by polymerase chain reaction (PCR) using osmotin and npt II specific primers. Infection with P. capsici on detatched leaves of putative transgenics showed delayed infection and decreased rate of disease spread indicating differential expression of osmotin. Stem and leaf inoculated plants showed survival, while root inoculated plants succumbed to infection and died. It can be inferred that osmotin confers resistance to infection by Phytophthora capsici in black pepper.